Czy badacze jakościowi wiedzą co widzą, a osoby badane wiedzą co mówią? O jakości danych jakościowych - Trusz , Sławomir (Studia Edukacyjne, 2020)
Trusz Sławomir, Czy badacze jakościowi wiedzą co widzą, a osoby badane wiedzą co mówią? O jakości danych jakościowych [Do Qualitative Researchers Know what They See and do the Subjects Know what They Say? On the Quality of Qualitative Data]. Studia Edukacyjne nr 56, 2020, Poznań 2020, pp. 199-219. Adam Mickiewicz University Press. ISSN 1233-6688. DOI: 10.14746/se.2020.56.11 Empirical data collected through qualitative methods may be more or less reliable and valid. The paper describes cognitive and social factors affecting credibility of information obtained by means of non-standardized observation and interview. The aforementioned issue was illustrated by the results of investigation on the change blindness and false memories phenomena. Finally, the procedures for improving the quality of qualitative data and, consequently, the reasonableness of conclusions regarding the analyzed social phenomena were discussed.